PELATIHAN EDPUZZLE SEBAGAI INTERACTIVE TEACHING MEDIA DI SMART INDONESIA - Kasriyati, Destina; Novitasari, Yesi; Suharni, Suharni (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2024)
Teachers are still unable to fully control the entire multimedia-based learning process. This is due to the minimum learning management system (LMS) development training followed by teachers in the school. Training organized by policy organizers can often only be followed by one teacher from each school. Taking into account the problems faced by the partners, the community dedication team has provided Edpuzzle training as an interactive learning resource at the partner schools. The event was conducted and attended by seven participants, namely, the teachers of the partner schools. The results of this activity have positive benefits and get a good response from the teachers. In addition to the training results, there was an increase in the participants' knowledge about the Edpuzzle.